2015
DOI: 10.3109/2000656x.2015.1029935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk of post-operative bleeding complications in skin cancer surgery without interruption of anticoagulant/antithrombotic medication: A prospective cohort study

Abstract: Skin cancer surgery can be safely performed without discontinuation of AC/AT treatment, since the risk of postoperative bleeding is statistically insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
13
0
6
Order By: Relevance
“…Aufgrund unzureichender Präzision ist unklar, ob das perioperative Fortführen von ASA das Risiko für leichte postoperative Blutungen erhöht (RD 0,003, 95 %‐KI –0,05 bis 0,04; Qualität der Evidenz: sehr niedrig). –Signifikante postoperative Blutungen (Abbildung 2c): Sieben Studien berichteten über diesen Outcome. Zwei Studien [26, 27], die in keinem der beiden Studienarme ein Ereignis berichteten, wurden nicht in die Metaanalyse aufgenommen (n = 280). Die Daten von Eichhorn et al.…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…Aufgrund unzureichender Präzision ist unklar, ob das perioperative Fortführen von ASA das Risiko für leichte postoperative Blutungen erhöht (RD 0,003, 95 %‐KI –0,05 bis 0,04; Qualität der Evidenz: sehr niedrig). –Signifikante postoperative Blutungen (Abbildung 2c): Sieben Studien berichteten über diesen Outcome. Zwei Studien [26, 27], die in keinem der beiden Studienarme ein Ereignis berichteten, wurden nicht in die Metaanalyse aufgenommen (n = 280). Die Daten von Eichhorn et al.…”
Section: Ergebnisseunclassified
“…Clopidogrel versus kein Clopidogrel –Signifikante postoperative Blutungen (Abbildung 2d): Drei Studien [27, 29, 30] mit insgesamt 1593 Teilnehmern wurden zusammengeführt. Aufgrund unzureichender Präzision ist unklar, ob das perioperative Fortführen von Clopidogrel das Risiko signifikanter postoperativer Blutungen erhöht (RD 0,02, 95 %‐KI –0,02 bis 0,05; Qualität der Evidenz: sehr gering).…”
Section: Ergebnisseunclassified
“…Due to imprecision, it is uncertain whether the perioperative continuation of ASA increases the risk of minor postoperative bleedings (RD 0.003, 95 % CI –0.05 to 0.04; quality of evidence: very low). –Significant postoperative bleeding (Figure 2c): Seven studies reported on this outcome. Two studies [26, 27], which did not report an event in either study arm, were not included in the meta‐analysis (n = 280). Data collected by Eichhorn et al.…”
Section: Resultsmentioning
confidence: 99%
“…En nuestro estudio, el 28.1% de los pacientes utilizaban antiagregantes y el 4.3% algún tipo de anticoagulación, mismos que continuaron durante el procedimiento (Tabla 2). Solo se reportó un paciente con hemorragia (0.2%) sin antecedente de terapia antitrombótica, porcentaje más bajo que el referido en el estudio de Shimizu, et al 28 , en el cual solo cuatro pacientes (0.53%) de 760 presentaron hemorragia, resultado similar al del estudio de Shipkov, et al 14 , con un solo paciente con hemorragia y uso de anticoagulante. Bordeaux, et al 29 , en su estudio, reportan un 0.89% de complicaciones hemorrágicas, la mayoría asociadas con el uso de anticoagulantes.…”
Section: Discussionunclassified
“…-Hemorragia: presencia de hematoma o persistencia de sangrado en las 24 horas posteriores al procedimiento, que requirieran reintervención para ligar un vaso sangrante o para drenaje de hematoma 14 . -Infección: presencia de exudado purulento, incremento de temperatura local, eritema perilesional y dolor progresivo en las primeras 72 horas posquirúrgicas.…”
Section: Análisis Estadísticounclassified